Beyond drugs: TB patients in Bangladesh need urgent attention for nutrition support during convalescence - Islam, Qazi Shafayetul; Ahmed, Syed Masud; Islam, Md. Akramul; Kamruzzaman, Md.; Rifat, Mahfuza (BRAC Research and Evaluation Division (RED), 2019)
Tuberculosis (TB) is a global disease, which is responsible for 1.4 million deaths each year (WHO 2010). Bangladesh is the sixth highest TB-burden country in the world. TB treatment may be complicated when malnutrition also coexists in patients. TB has been found to coexist with malnutrition among patients at the beginning of treatment in both developed and developing countries (Zachariah eta/. 2002, Onwubalili JK 1988, Kennedy et at. 1996, Harries et a/. 1988). Nutrition supplementation can play an important role in improving the disease condition to reduce further morbidity and mortality. Some TB-burden countries have already started food supplementation programme for patients' healthy life (Farmer eta/. 1991, Karyadi et a/. 2002, Paton et a/. 2004, Aye and Wyss 2009). There is no nutrition intervention programme for patients in DOTS (Directly observed treatment, short course) approach to TB treatment under National TB Control Programme (NTP) of Bangladesh, where malnutrition is prevalent. Even, Bangladesh does not have much information about the nutritional situation of TB patients to formulate nutrition intervention. To fill-in this knowledge gap and help in informed design of a nutrition intervention for TB patients, this study measured the nutritional status (using Body Mass Index or BMI) of TB patients before, at two months, and after completion of TB treatment (DOTS) to study the changes during treatment and its relation with various socioeconomic and demographic factors including household food availability and consumption.